Oldest Chasicotatus (Cingulata, Xenarthra) remains give a new approach to this lineage biochron and taxonomic status - Barasoain Goñi, Daniel (2020)
Eutatini armadillos are a tribe within the subfamily Euphractinae (Chlamyphoridae), characterized by large piliferous foramina and the absence of a well-defined carapace scapular buckler. Though there are no living representatives, they are present in the fossil record from late Eocene to Holocene deposits of southern South America. Here we report new materials (CTESPZ-7852, isolated osteoderms) assigned to the genus Chasicotatus Scillato-Yané from Cañadón del Tordillo site (Colloncuran SALMA) of Neuquén Province (Argentina). This represents the southern record of the genus and extends its biochron by ~6 Ma (previously recorded in ~9?10 Ma). Though the genus Stenotatus Ameghino was the only Eutatini recorded for the Colloncuran SALMA so far, remains are assigned to Chasicotatus according to traditional diagnosis based on dorsal carapace features; including a flat transitional zone between articular and caudal portions of mobile osteoderms, a more dorsal orientation of the piliferous foramina of the osteoderms, and a more extended main figure of osteoderms ornamentation, that reaches the posterior margin of the osteoderm, unlike in Stenotatus. These same characters have been used from the first descriptions of these taxa without being later discussed. However, it is to remark that the morphological variability that they present in current Euphractinae armadillos such as Chaetophractus villosus Desmarest, or even in other groups such as Dasypodinae or Tolypeutinae, suggests the future need of more detailed revisions in order to verify their validity and/or the identification of new more robust diagnostic characters that allow to keep supporting the validity of these two taxa.